2011
DOI: 10.3758/s13415-011-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Processing the emotions in words: The complementary contributions of the left and right hemispheres

Abstract: A dual-process model is suggested for the processing of words with emotional meaning in the cerebral hemispheres. While the right hemisphere and valence hypotheses have long been used to explain the results of research on emotional stimulus processing, including nonverbal and verbal stimuli, data on emotional word processing are mostly inconsistent with both hypotheses. Three complementary lines of research data from behavioral, electrophysiological, and neuroimaging studies seem to suggest that both hemispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 108 publications
(165 reference statements)
4
30
1
8
Order By: Relevance
“…Abbassi and colleagues [65] further proposed that emotional information is automatically activated when processed by the left hemisphere. Given that the target stimuli were presented for 150 ms in this study, the observed differences between left and right hemispheric processing seem consistent with the assumption of an early locus of this effect in the word recognition stream.…”
Section: Discussionmentioning
confidence: 99%
“…Abbassi and colleagues [65] further proposed that emotional information is automatically activated when processed by the left hemisphere. Given that the target stimuli were presented for 150 ms in this study, the observed differences between left and right hemispheric processing seem consistent with the assumption of an early locus of this effect in the word recognition stream.…”
Section: Discussionmentioning
confidence: 99%
“…Enquanto o HE está mais envolvido na modulação dos componentes proposicionais da linguagem, o HD está relacionado com a modulação de componentes afetivos (Wymer, Lindman, & Booksh, 2002), principalmente em emoções negativas (Abbassi et al, 2011).…”
Section: Discussionunclassified
“…"Emotional words trigger activation in other areas of the LH, such as the amygdala, orbitofrontal cortex, and posterior cingulate gyrus, as well. These regions have been claimed to be part of the limbic system (see Figure 2), which plays a key role in emotion processing" (Abbassi, Kahlaoui, Wilson, & Joanette, 2011). "The data from a large body of research based on behavioral, electrophysiological, and neuroimaging methodologies appear to converge in indicating that both hemispheres are involved in the processing of words with emotional meaning, albeit in different, and probably complementary, ways."…”
Section: Discussionmentioning
confidence: 99%